Perbandingan Algoritma Bee Colony dengan Algoritma Bee Colony Tabu List dalam Penjadwalan Flow Shop - Andre Sugioko (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2013)
This paper discusses the performance of Bee Colony algorithm integrated with the swap method and tabu listwith Bee Colony algorithm. This research was based on the results of research by Chong in 2006, whichdeclared that the Bee Colony algorithm integrated with the swap method has a good performance, but cannotcompete with the performance of Tabu Search, so the researchers will test whether integrating Bee Colonyalgorithm with swap method and tabu list will give better performance than Bee Colony algorithm or not.This research will use two study case flow shop scheduling problem, with objective function is minimummakespan to compare both algorithm’s performance. The results Bee Colony-Tabu provide superior resultsat makespan values than Bee Colony algorithm, but not at computational time.